Chemical Composition and Cytotoxic and Antioxidant Activities of Satureja montana L. Essential Oil and Its Antibacterial Potential against Salmonella Spp. Strains - Hanene Miladi; Rihab Ben Slama; Donia Mili; Sami Zouari; Amina Bakhrouf; Emna Ammar (Journal of Chemistry)
The present study describes chemical composition as well as cytotoxic, antioxidant, and antimicrobial activities of winter savory Satureja montana L. essential oil (EO). The plant was collected from south France mountain, and its EO was extracted by hydrodistillation (HD) and analysed by gas chromatography/mass spectrometry (GC/MS). Thirty-two compounds were identified accounting for 99.85% of the total oil, where oxygenated monoterpenes constituted the main chemical class (59.11%). The oil was dominated by carvacrol (53.35%), γ-terpinene (13.54%), and the monoterpenic hydrocarbons p-cymene (13.03%). Moreover, S. montana L. EO exhibited high antibacterial activities with strong effectiveness against several pathogenic food isolated Salmonella spp. including S. enteritidis with a diameter of inhibition zones growth ranging from 21 to 51 mm and MIC and MBC values ranging from 0.39–1.56 mg/mL to 0.39–3.12 mg/mL, respectively. Furthermore, the S. montana L. EO was investigated for its cytotoxic and antioxidant activities. The results revealed a significant cytotoxic effect of S. montana L. EO against A549 cell line and an important antioxidant activity. These findings suggest that S. montana L. EO may be considered as an interesting source of components used as potent agents in food preservation and for therapeutic or nutraceutical industries.